Bridging the Digital Divide to Improve Village Governance for Global Efficiency: Menjembatani Kesenjangan Digital untuk Meningkatkan Tata Kelola Desa demi Efisiensi Global - Khoiroh, Mazroul; Fitria Agustina, Isna (Indonesian Journal of Public Policy Review, 2024)
This study analyzes the performance of village officials in Glagaharum Village's administrative services using a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed using Miles and Huberman's techniques. Evaluated through T. R. Mitchell's indicators—Work Quality, Communication, Timeliness, Ability, and Initiative—the findings reveal that while technical guidance improves service quality, communication and technological challenges persist. Many officials lack technological skills, affecting service timeliness and initiative. The study highlights the need for targeted training to enhance officials' technological proficiency and improve overall service delivery. Highlights: Targeted Training: Improve officials' technological skills. Communication Struggles: Address difficulties with online services. Timeliness Concerns: Online service issues hinder punctuality. Keywords: Village administration, performance evaluation, qualitative research, service delivery, technological skills